Cerebral Plasmodium falciparum malaria: The role of PfEMP1 in its pathogenesis and immunity, and PfEMP1‐based vaccines to prevent it - Jensen, Anja Ramstedt (Immunol Rev, 2019)
Malaria, a mosquito‐borne infectious disease caused by parasites of the genus Plasmodium continues to be a major health problem worldwide. The unicellular Plasmodium‐parasites have the unique capacity to infect and replicate within host erythrocytes. By expressing variant surface antigens Plasmodium falciparum has evolved to avoid protective immune responses; as a result in endemic areas anti‐malaria immunity develops gradually over many years of multiple and repeated infections. We are studying the role of Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) expressed by asexual stages of P. falciparum responsible for the pathogenicity of severe malaria. The immunopathology of falciparum malaria has been linked to cyto‐adhesion of infected erythrocytes to specific host receptors. A greater appreciation of the PfEMP1 molecules important for the development of protective immunity and immunopathology is a prerequisite for the rational discovery and development of a safe and protective anti‐disease malaria vaccine. Here we review the role of ICAM‐1 and EPCR receptor adhering falciparum‐parasites in the development of severe malaria; we discuss our current research to understand the factors involved in the pathogenesis of cerebral malaria and the feasibility of developing a vaccine targeted specifically to prevent this disease.